An Approach to the Dynamics of Vibration-driven Robots with Bristles. Issue 1 (2015) - Becker, Felix
Abstract: In this paper, a rigid body model of vibration-driven robots with bristles is presented and studied numerically. Bristles provide asymmetric friction properties to transform the vibrations of internal masses to a directed locomotion. The aim of this study is to investigate the motion principle of robots with bristles based on mechanical models and to find the influence of system parameters to the locomotion velocity.